Faba beans for biorefinery feedstock or feed? Greenhouse gas and energy balances of different applications. (December 2015) - Karlsson, Hanna; Ahlgren, Serina; Strid, Ingrid; Hansson, Per-Anders
Abstract: Legumes have been proposed as biorefinery feedstock primarily due to their low nitrogen fertilizer demand, low fossil energy-related greenhouse gas emissions and high protein content, enabling efficient protein feed, food or amino acid production. Grain legumes (pulses) occupy approx. 1.2% of the arable land in Sweden, with faba bean, which is used as a protein feed, being one of the most common. Utilization of the whole crop, including the beans and the remaining aboveground biomass, can enable co-production of feed, food and/or fuel in high quantities, as faba bean has potentially high total biomass yield. In this study, Consequential Life Cycle Assessment (CLCA) was used to analyze a change from the current use of faba bean as protein feed for dairy cows (Reference scenario) to two alternative uses where the whole crop is harvested: whole crop processing in a green biorefinery producing ethanol, protein concentrate feed and fuel briquettes (Biorefinery scenario), or with the whole crop used as roughage feed (Roughage scenario). Impacts on climate change, arable land use and primary fossil energy use were considered. The changed use of faba bean resulted in changes in the feedstuff requirements for dairy cows, which were highly influential for the results. Whole crop harvesting as opposed to bean harvesting with return of crop residues resulted in increased climate impact and energy use during the agricultural and processing stages. On including substitution effects of the products, the Biorefinery scenario resulted in + 25, − 20% and − 100% change for climate impact, arable land use and energy use, respectively, in relation to the Reference situation. The increase in climate impact was primarily due to soil carbon changes and increased demand for marginal grain. When the whole faba bean crop was used as roughage (Roughage scenario), the corresponding changes were + 164%, − 130% and + 167% for climate change, arable land use and energy use, respectively. The increased impact was due to increased use of feed grain as a result of using the protein-rich roughage. Highlights: We apply CLCA to model changed use of faba bean including biorefinery processing. Faba bean used as biorefinery feedstock lowered fossil energy use and land use. Soil organic carbon effects due to whole crop harvesting were highly influential. Feed use effects due to changed use of faba bean greatly influenced the results.